Parents'/carers' perceptions and experiences of growing, preparing and eating their own fruit and vegetables as part of the 'Field to Fork' project. Issue 6 (1st November 2016) - Burton, Diana M.; May, Stephanie
Abstract : This paper reports research into a project to encourage KS1 and KS2 pupils to eat more healthily by supporting their families to grow their own fruit and vegetables at home. Participants were recruited through a Primary School Trust comprising four primary schools in the North West of England. They were given practical support to enable them to grow fruit and vegetables. The findings of pre-programme focus groups with parents/carers suggested families tended not to eat the daily government-recommended five portions of fruit and vegetables; cost, time and knowledge being the main inhibitors. With resources, knowledge and support most participants were enabled to grow their own fruit and vegetables leading to increased consumption. Availability to and familiarity with fresh fruit and vegetables by tending and growing them first-hand was shown to increase their consumption.